Mechanisms and model of structure formation in metals during severe deformation - Utyashev, F.Z.; Raab, G.I. (Физика и техника высоких давлений, 2006)
It is established that extremely fine fragments and grains are formed when the value of the accumulated curvature in metals increases to the value equal to the maximum tensor density of dislocations. This is provided by the high value of the ratio between the surface area of deformation center and its volume. Depending on scale factor that influences the development of interfragment deformation and contribution of surface dislocation sources into the deformation process, the fragmented structure either stabilizes or there occurs the phase change from a crystal state to an amorphous one.